2005
DOI: 10.1176/jnp.17.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress During Treatment With First- and Second-Generation Antipsychotics

Abstract: Neurotoxicity of first-generation antipsychotics (FGAs) may be involved in lipid peroxidation, which is the pathogenesis of extrapyramidal symptoms, including tardive dyskinesia (TD). Blood samples at day 0, 7, and 21 drawn from patients taking antipsychotics were analyzed for malondialdehyde (MDA) in plasma, a marker of lipid peroxidation, by high-performance liquid chromatography. Of 115 patients enrolled, 92 patients completed the study. Most MDA levels were within normal ranges (<1.0 micromol/liter). Malon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…The level of lipid peroxidation (measured by the levels of TBARS) was significantly higher after the incubation with haloperidol than after amisulpride. These results are similar to previous results of animal studies and a few clinical observations of TBARS levels in patients treated with antipsychotics are described [42,44,45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The level of lipid peroxidation (measured by the levels of TBARS) was significantly higher after the incubation with haloperidol than after amisulpride. These results are similar to previous results of animal studies and a few clinical observations of TBARS levels in patients treated with antipsychotics are described [42,44,45].…”
Section: Discussionsupporting
confidence: 92%
“…It should be mentioned that therapy with antipsychotic drugs may affect lipid metabolism [41]. Classical antipsychotic drugs may exhibit prooxidative effects [14,41], whereas the second generation antipsychotic drugs do not exhibit such effects, moreover they may have even antioxidative effects [14,42]. The earlier [43] and presented study also showed a significant different action of FGA (haloperidol) and SGA (amisulpride) on plasma lipid peroxidation.…”
Section: Discussionmentioning
confidence: 65%
“…Higher levels of lipid peroxidation products have been reported in patients treated with typical than atypical drugs (Kropp et al, 2005), but contradictory results were reported by others (Gama et al, 2006;Zhang et al, 2006a). The differing pro-oxidant potentials of the antipsychotics have been postulated as a mediating factor in the more common development of tardive dyskinesia with typical agents (Andreassen and Jorgensen, 2000).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Ketamine, a dissociative anesthetic and an NMDA antagonist, has been shown to cause schizophrenialike symptoms in humans and is widely used in rodents to create a condition mimicking schizophrenia [28,30]. Oxidative stress has been strongly implicated in the development of schizophrenic symptoms and evidence of lipid peroxidation and protein oxidation/nitration has been found in the plasma of schizophrenic subjects [5,9,36,37]. Here we studied oxidative stress in the brain of mice treated with ketamine alone or with the antipsychotic drugs clozapine and haloperidol.…”
Section: Discussionmentioning
confidence: 99%